Sovereign Insurance and Program Design : What is Optimal for the Sovereign? - Messmacher, Miguel (IMF Working Papers; Working Paper, 2006)
The design of the optimal sovereign insurance contract is analyzed when: the sovereign chooses the contract; effort is not contractible; shocks are of uncertain magnitude; the sovereign can save; and the sovereign can default. Under these conditions: i) an ex ante premium leads to higher coverage; ii) the premium increases with the sovereign's incentive to take risks; iii) a deductible is chosen to limit moral hazard; iv) the deductible-to-support ratio is decreasing with the size of the realized shock; and v) the change in the choice of savings when insurance is available is ambiguous, as there is a trade-off between inducing higher effort and increasing the likelihood of default.